Hubungan Produktivitas dengan Tingkat Kesejahteraan Petani Jambu Mete di Desa Pebaoa Kecamatan Kulisusu Utara Kabupaten Buton Utara - Herlina Wati; Hidrawati Hidrawati; Muhammad Aswar Limi (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
A study to determine the relationship between productivity and welfare level of cashew farmers. The welfare group consists of several indicators: income, house construction, and children's education level. This research was conducted ini Pebaoa Village, North Kulisusu District, Nort Buton Regency, from August to September 2021. The data analysis used in this study is a quantitative descriptive analysis technique using the Chi-Square test formula (X2). The population of this study amounted to 182 farmers. Sampling was done at a simple random sampling by taking an error rate of 15% and obtaining a sample of 35 farmers. Primary data and secondary data are the two forms of data. Preliminary data was gathered by direct observation and questionnaire interviews with respondents, while secondary data was collected through entities involved in the study. The findings revealed a link between productivity and farmer well-being markers, such as income, housing style, and children's education level. The X2 value obtained from each welfare indicator is 5,07; 4,5 and 4,94, which are more significant than the table X2 value at the 95% confidence level.